EFFECTS OF VESTIBULAR EXERCISES ON POSTURAL BALANCE FOR CHILDREN - Kaupužs, Aivars; Lāriņš, Viesturs; Rižakova, Lorita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The balance is one of the most important skills of the postural control and ability to move. The data are gained during the research that was supported by National Research Program "Innovative solutions in social rehabilitation in Latvian schools in the context of inclusive education". The balance sway index (SI) was tested by digital platform BioSway. The research group included 8 boys and 7 girls in the 12-14 years age range with vestibular function insufficiency. The aim of the study was to examine the immediate effect of vestibular exercises and to evaluate the degree of postural balance parameter changes after vestibular exercises complex applications. Vestibular exercise with head rotation 20 seconds with 3 repetitions caused statistically significant (p- 0.03) increasing of SI. The statistically significant (p- 0.025) improvement of SI was set after vestibular rehabilitation exercises complex application during 6 weeks (10-15 minutes a day).